Real-Time Noise Cancellation Using Adaptive Algorithms - Hameed, Alaa Ali (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: The contamination of a signal of interest by other undesired signals (noise) is a problem encountered in many applications. The conventional linear digital filters with fixed coefficients exhibit a satisfactory performance in extracting the desired signal when the signal and noise occupy fixed and separate frequency bands. However, in most applications, the desired signal has changing characteristics which requires an update in the filter coefficients for a good performance in the signal extraction. Since the conventional digital filters with fixed coefficients do not have the ability to update their coefficients, adaptive digital filters are used to cancel the noise. The mean square error (MSE) technique is used as a measure of the noise reduction. The adaptive filter generally uses finite impulse response (FIR) least-mean-square (LMS) and normalized LMS (NLMS) algorithms in signal processing or infinite impulse response (IIR) recursive-least-squares (RLS) algorithm in adaptive control for the noise cancellation applications. The main aim of this thesis is to investigate the implementation of a real time noise cancellation application. The real time implementation is carried out by a Texas Instruments (TI) TMS320C6416T Digital Signal Processor (DSP). First, the LMS, NLMS and RLS algorithms are simulated using SIMULINK of MATLAB. Then, these algorithms have been transferred to the DSP board which let, them to work alone in real time independent of MATLAB. Furthermore, the performance of the aforementioned algorithms has been compared in different problem settings. Keywords: Adaptive Filters, FIR Filters, IIR Filters, LMS Algorithm, NLMS Algorithm, RLS Algorithm. ………………………………………………………………………………………………………… ÖZ: Bir sinyalin, istenmeyen sinyal (gürültü) tarafından kirlenmesi birçok uygulamada karşı karşıya kalınan bir problemdir. Geleneksel sabit katsayılı doğrusal sayısal süzgeçler, sinyal ve gürültü sabit ve ayrı frekans bandlarını işgal ettiği zaman, istenen sinyalin elde edilmesi için yeterli bir performans sergilerler. Bununla birlikte, birçok uygulamada, istenen sinyalin değişen karakteristikerinden dolayı sinyal elde işleminde iyi bir performans elde etmek için süzgeç katsayılarında bir güncellemeye ihtiyaç duyulmaktadır. Geleneksel sabit katsayılı sayısal süzgeçlerin katsayılarını güncelleme yeteneği olmadığı için gürültüyü yok etmek için uyarlanabilir sayısal süzgeçler kullanılmaktadır. Ortalama–kare-hata tekniği gürültü azaltma ölçümü olarak kullanılır. Uyarlanabilen sayısal süzgeç, genellikle sonlu-dürtü-cevabı (FIR) enaz-ortalama-kare (LMS) ve normalize olmuş LMS (NLMS) algoritmalarını sayısal sinyal işleme alanında veya sonsuz-dürtü-cevabı (IIR) tekrarlanan-enaz-kare (RLS) algortimasını gürültü yoketme uygulamalarında kullanır. Bu tezin esas amacı gerçek zamanda bir gürültü yoketme uygulamasını araştırmaktır. Gerçek zaman uygulaması, Texas Instruments TMS320C6416T sayısal sinyal işlemcisi ile MATLAB‘ın Simulink ortamında yapılmıştır. İlk olarak, LMS, NLMS ve RLS algoritmalarının benzetimi yapılmıştır. Daha sonra, bu algoritmalar sayısal sinyal işlemcisine transfer edilerek sayısal sinyal işlemcisinin MATLAB’dan bağımsız olarak gerçek zamanda kendi başına çalışması sağlanmıştır. Ayrıca, adı geçen algoritmaların performansı farklı problemler için karışlaştırılmıştır. Anahtar kelimeler: Uyaranabilir süzgeçler, FIR süzgeçler, IIR süzgeçler, LMS algoritması, NLMS algoritması, RLS algoritması, EDICATION.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2012. Supervisor: Prof. Dr. Hasan Kömürcügil.
Keywords: Computer Engineering; Speech Processing Systems - Automatic Control; Adaptive Filters - FIR Filters - IIR Filters - LMS Algorithm - NLMS Algorithm - RLS Algorithm